Pengaruh Kualitas Pelayanan Dan Harga Terhadap Kepuasan Konsumen Produk Fashion Di Matahari Depok Town Square Kota Depok - Sabarulloh Sabarulloh; Erlita Kurniawaty (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstrak. This study aims to determine the effect of service quality and price on consumer satisfaction at Matahari Depok Town Square Depok, both partially and simultaneously. The type of research uses an associative quantitative method. The sampling technique uses random samples using the slovin technique and 99 consumers were obtained as respondents. The results of the analysis show: Service Quality has an effect on consumer satisfaction at Matahari Depok Town Square, as evidenced by the value of the equation t count> t table or 2.591> 1.987, thus H0.1 is rejected and Ha.1 is accepted, meaning that there is a positive and significant effect between Service Quality (X1) on Consumer Satisfaction (Y) at Matahari Depok Town Square. Price partially has a positive effect on consumer satisfaction at Matahari Depok Town Square, as evidenced by the value of t count> t table or 4.855> 1.987, thus H0.2 is rejected and Ha.2 is accepted, where there is a positive and significant effect between Price (X2) on Purchasing Decisions (Y) at Matahari Depok Town Square. Service quality and price simultaneously have an influence on consumer satisfaction at Matahari Depok Two Square, as evidenced by the Fcount of 198.221 and the Ftable value of 0, while the Ftable value at the 0.05 level with df 1 (number of variables -1) 3-1 = 2, and df 2 (n-k-1) or = 99-2-1 = 96 obtained the Ftable value of 3.09. So it can be concluded that Fcount> Ftable (198.221> 3.09) and the Ftable value <0.05 (0 <0.05), then Ha is rejected, so it can be concluded that Service Quality and Price together have an influence on Consumer Satisfaction. Keywords: Service Quality, Price, Consumer Satisfaction.